ANALYSIS OF NOSOLOGIES AND MEDICINES USED BY THE APPLICANTS OF HIGHER MEDICAL EDUCATION AT PRE- AND POSTGRADUATE LEVELS (BY THE RESULTS OF SOCIOLOGICAL RESEARCH) - Zaremba, N.I.; Zimenkovskyi, A.B. (The Ukrainian Scientific Medical Youth Journal, 2018)
Purpose of the study is the analysis of nosologies and medicines used in self-treatment by the applicants of higher medical education.Materials and methods of research. The scientific work performed on the results of a sociological study involving 400 applicants of education at pre- and postgraduate levels at Danylo Halytsky Lviv National Medical University.Results and discussion. The majority of surveyed (56,50±2,48 %) did not systematically take analgesics, mainly with headache. However, only 4,75±1,06 % questioned with feeling heaviness in the stomach always took enzymes. The vast majority of questioned (79,25± ±2,03 %) had never taken BAAs. It was found out that the respondents took medicines from the groups of non-narcotic analgesics, vitamins and antispasmodic remedies during the last month. The most frequent reasons why surveyed took medications regularly were infectious and gastrointestinal diseases. Extremely rarely questioned with diseases of the musculoskeletal system and the eye took drugs constantly. 29,75±2,29 % respondents had cases of combination of alcohol and drugs. The side effects and high costs of medicines were the most often noted among the factors causing warning of surveyed in pharmacotherapy. A three times lower specific weight of questioned indicated a lack of drugs in pharmacies; lack of knowledge of the mechanism of action and interaction with other medicines. In the overwhelming majority (75,50±2,15 %) medications influenced the quality of their lives by improving well-being and working capacity. However, every 7th respondent had side effects of medicines. In our opinion, the obtained results should serve as the basis for working out a comprehensive model of the program of prevention of negative consequences of self-treatment, first of all among young people.Conclusions. In our opinion, the obtained results should serve as the basis for working out a comprehensive model of the program of prevention of negative consequences of selftreatment, first of all among young people.